Sumber-sumber informasi elektronik Islami - Zulfitri Zulfitri (Al Maktabah, 2017)
The development of information and technology science can help librarians and users in informa-tion tracking. Internet services can facilitate a variety of information, both in the form of ebooks and ejournal. While electronic information is a new source of information can be read or used when already connected or using electronic media such as computers, lektop and notebook. The sources of electronic information, especially in the field of Islaman there is a program that must be installed into a laptop or computer such as Maktabah Syamilah program and there is a collection of ebook or ejournal that can be downloaded using internet facilities, such as a collection of software books Ara-bic as well as an online source of information online such as Maktabah Waqfeyah and Lisan Arabiy.